Genetic parameters of growth and resistance to Polydora ciliata in the pearl oyster Pinctada fucata. (16th April 2016) - Liu, Baosuo; Tan, Caigang; Zhang, Dongling; Chen, Mingqiang; Niu, Zhikai; Huang, Guiju; Li, Youning; Zhang, Tianshi; Yu, Dahui
Abstract: The pearl oyster Pinctada fucata is an economically important oyster cultured for pearl production in China. In this study, we used an animal model to estimate the variance components and genetic parameters of growth traits and a sire‐dam threshold model to estimate the resistance of P. fucata to polychaete Polydora ciliata . The results showed that the heritability estimates were 0.3850 ± 0.1421 for shell width, 0.3478 ± 0.1292 for body weight and 0.3387 ± 0.1316 for resistance to P. ciliata, and significantly different from zero ( P  < 0.05). Both phenotypic and genetic correlations were high between shell width and body weight (0.935 and 0.883 respectively) ( P  <   0.01), but low between resistance and shell width (0.260 and 0.233 respectively)/body weight (0.152 and 0.083 respectively) ( r  < 0.30; P >  0.05). The higher heritabilities for shell width, body weight and resistance traits suggested that the three traits can be genetically improved through selective breeding, but the low correlation between growth and resistance traits suggested that the resistance trait can be effectively improved through index selection or through hybridization of two specialized lines, i.e. a high‐resistant line and a high growth line.